Production of sulfate radical from peroxymonosulfate induced by a magnetically separable CuFe2O4 spinel in water: efficiency, stability, and mechanism - Zhang, T.; Zhu, H.; Croué, Jean-Philippe (American Chemical Society, 2013)
A simple, nonhazardous, efficient and low energy-consuming process is desirable to generate powerful radicals from peroxymonosulfate (PMS) for recalcitrant pollutant removal. In this work, the production of radical species from PMS induced by a magnetic CuFe2O4 spinel was studied. Iopromide, a recalcitrant model pollutant, was used to investigate the efficiency of this process. CuFe2O4 showed higher activity and 30 times lower Cu2+ leaching (1.5 µg L-1 per 100 mg L-1) than a well-crystallized CuO at the same dosage. CuFe 2O4 maintained its activity and crystallinity during repeated batch experiments. In comparison, the activity of CuO declined significantly, which was ascribed to the deterioration in its degree of crystallinity. The efficiency of the PMS/CuFe2O4 was highest at neutral pH and decreased at acidic and alkaline pHs. Sulfate radical was the primary radical species responsible for the iopromide degradation. On the basis of the stoichiometry of oxalate degradation in the PMS/CuFe 2O4, the radical production yield from PMS was determined to be near 1 mol/mol. The PMS decomposition involved an inner-sphere complexation with the oxide's surface Cu(II) sites. In situ characterization of the oxide surface with ATR-FTIR and Raman during the PMS decomposition suggested that surface Cu(II)-Cu(III)-Cu(II) redox cycle was responsible for the efficient sulfate radical generation from PMS.